Extension work or innovation as process of social and group learning. Where is the dilemma? - Rodr?guez, L.; la O, M.; Fonseca, Mar?a; Hern?ndez, Araceli; Jim?nez, Madel?n (Cuban Journal of Agricultural Science, 2009)
A critical theoretical and practical analysis of the concepts of innovation, extension work, and transfer of technology is performed. According to them and their methodological basis and limitations, some alternatives of the linear model of technology transfer are provided. An alternative proposal of innovation is discussed, in which the development of effective alliances and the understanding and synthesis of shared insights are key to face challenges and problems of the environment, more complex and changing every time. Finally, some emerging ideas are provided about a new methodological proposal to manage processes of innovation at local level. Key words: innovation, extension work, technology transfer.